Effect of the Meteorological Conditions to Spring Water Availability in Some Karst Region at Gunungkidul Districts (Meteorologist Water Balance Analysis Study for Drought Mitigation) - Darmanto, Darmakusuma; Cahyadi, Ahmad (Universitas Muhammadiyah Surakarta, 2013)
The objective of this study is to understand the influence of meteorological conditions of logva water availability in karst area, Gunungkidul Regency. Meteorological condition analysis was determined by creating meteorological water balance using Thornthwaite Mather method. Water availability condition was determined by using multi-temporal images. Then, the result of water balance was matched with the logva water availability derived from multi-temporal images. The result shows that meteorological conditions will influence logva water availability in karst area, Gunungkidul Regency. It was shown by comparing the amount of logva in surplus months and deficit months. The amount of logva in surplus months is more than in deficit months. In addition, the longer meteorological water deficit, the amounts of detected logva decreases. Based on that condition, it means that meteorological water balance analysis can be used to plan disaster mitigation based on the time and duration of deficit months.